Peningkatan Kemampuan Pengelolaan Keuangan Rumah Tangga pada Ibu-Ibu RPTRA Sungai Bambu Jakarta Utara - Mary Ismowati; Muhammad As’ad; Rame Soekarsono; Nidaul Izzah; Didit Mulyadi; Ma’mun Ma’mun; Moh. Mujakir (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
Managing personal finances is a reality that must be faced by everyone in everyday life, where a person must be able to manage his personal finances and his household well in order to balance between income and expenses, to meet all the necessities of life and not get caught up in financial difficulties. Managing personal and household finances is not an easy thing to do because there are only difficulties faced by everyone, where one of the difficulties faced is the phenomenon of consumer behavior that is growing rapidly in the community. Likewise, the problem faced by housewives in Sungai Bambu Kelurahan, Tanjung Priok Sub-district, North Jakarta, so that a household financial management training activity was held as a solution to the problem.Some factors that support the implementation of this activity are the great interest and enthusiasm of the mothers as participants of the activity so that the activity takes place smoothly and in an orderly manner. While the inhibiting factor is the limited time of training. This activity can increase knowledge and understanding of RPTRA Sungai Bambu Village, Tanjung Priok Subdistrict, North Jakarta, increase knowledge about tips to deal with obstacles in managing household finances RPTRA, Sungai Bambu Village, Tanjung Bambu District, North Jakarta District, and increase knowledge and understanding of the RPTRA of Sungai Bambu Village, Tanjung Priok District, North Jakarta about the need for halal financial resources in financial managementConsidering the magnitude of the benefits of the activity, then it is necessary to hold a Financial Management training for every woman or RPTRA in DKI Jakarta as well as the continuity and monitoring of the program.